Sources of airborne endotoxins in ambient air and exposure of nearby communities - a review - Rolph, Catherine A.; Gwyther, Ceri L.; Tyrrel, Sean F.; Nasir, Zaheer A.; Drew, Gillian H.; Jackson, Simon K.; Khera, Shagun; Hayes, Enda T.; Williams, Ben; Bennett, Allan; Collins, Samuel; Walsh, Kerry A.; et al. (MDPI, 2018)
Endotoxin is a bioaerosol component that is known to cause respiratory effects in exposed populations. To date, most research focused on occupational exposure, whilst much less is known about the impact of emissions from industrial operations on downwind endotoxin concentrations. A review of the literature was undertaken, identifying studies that reported endotoxin concentrations in both ambient environments and around sources with high endotoxin emissions. Ambient endotoxin concentrations in both rural and urban areas are generally below 10 endotoxin units (EU) m−3; however, around significant sources such as compost facilities, farms, and wastewater treatment plants, endotoxin concentrations regularly exceeded 100 EU m−3. However, this is affected by a range of factors including sampling approach, equipment, and duration. Reported downwind measurements of endotoxin demonstrate that endotoxin concentrations can remain above upwind concentrations. The evaluation of reported data is complicated due to a wide range of different parameters including sampling approaches, temperature, and site activity, demonstrating the need for a standardised methodology and improved guidance. Thorough characterisation of ambient endotoxin levels and modelling of endotoxin from pollution sources is needed to help inform future policy and support a robust health-based risk assessment process.
Keywords: bioaerosol; endotoxin; composting facilities; intensive farming; air pollution